PERAN PENDAPATAN USAHATANI UBI KAYU (Manihot Esculenta) TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA OELETSALA, KECAMATAN TAEBENU, KABUPATEN KUPANG. - Alle, Ardi; Suek, Johanna; Surayasa, Made Tusan (Buletin Ilmiah Impas, 2023)
Cassava is the main food source for the community after corn and rice. Map This cassava plays an important role in the production of cassava to meet household food needs. This study aims to determine cassava production, determine cassava income, determine household income and to determine the role of cassava income on household income in Oeletsala Village, Taebenu District, Kupang Regency. The research location was determined deliberately. The population in this study are farmers who do cassava farming spread across five hamlets in Oeletsala Village. There were 55 sample farmers who were taken randomly. The collected data is analyzed simply by using an analysis of costs, income and the role of cassava in household income with a classification of contribution measurements. 1. 0.00% -10% Very Poor, 2. 10.10% -20% Poor, 3. 20.10% -30% Moderate 4. 30.10% -40% Fairly Good, 5. 40.10 %-50% Good, 6. >50% Very Good. The research results show that 1). The amount of cassava production in the research area of ​​Oeletsala Village is the amount. 87,140.00 kg/land area (are) 2). The amount of cassava income in the research area of ​​Oeletsala Village with the number. Rp. 5,641,519.17 -/planting season with a total preset of 34.15% per planting season. 3). The total household income from all intercropped cassava farming and non-farming in the research area of ​​Oeletsala Village with a total of 46 respondents was Rp. 16,518,724.54 per growing season. 4). The role of cassava farming is obtained from the farmer's income in cassava farming divided by the total family income multiplied by 100%, so that the results of calculating the role of cassava on household income is 30.67%. Therefore, according to standard calculations, the role of cassava income is quite good according to the classification calculation of the contribution of 30.10% -40% which is quite good in Oeletsala Village, Kupang Regency.